Factor structure and internal consistency of a Swedish version of the Pain Catastrophizing Scale. Issue 2 (21st August 2018) - Kemani, Mike K.; Grimby‐Ekman, Anna; Lundgren, Jesper; Sullivan, Michael; Lundberg, Mari
Abstract : Background: Pain catastrophizing is highly relevant to assess in the context of long‐standing pain. The Pain Catastrophizing Scale (PCS) is a well‐established questionnaire used to measure catastrophizing in individuals with long‐standing pain. So far, no Swedish translation has been evaluated in regard to validity and reliability. The aims of this study were to translate the PCS questionnaire from English to Swedish, and to investigate its construct validity (face, content, and structural validity) and reliability (internal consistency). Methods: We translated the original English version of the PCS to Swedish and collected item responses from 194 persons suffering from primarily long‐standing musculoskeletal pain. We used confirmatory factor analysis to evaluate structural validity, and tested the model fit of a one‐factor model, an oblique two‐factor model, and an oblique three‐factor model. We evaluated the measure's reliability in regard to internal consistency calculated with Cronbach's alpha. Results: A three‐factor model comprising a four‐item rumination factor, a three‐item magnification factor, and a six‐item helplessness factor provided the best fit to the data. Internal consistency was adequate and Cronbach's α was 0.92 for the entire scale, 0.84 for the rumination subscale; 0.69 for the magnification subscale, and 0.89 for the helplessness subscale. Conclusions: The results indicated adequacy of a three‐factor solution and the questionnaire's internal consistency, and provide initial support for the structural validity and internal consistency of a Swedish version of the PCS. Future studies should replicate the study in larger samples and extend the current evaluation in regard to validity and reliability.